Wiedza organizacji a Homo symbolicus - Maj, Ireneusz (Organization's knowledge versus homo symbolicus, 2006)
The categories of knowledge and knowledge management have not been indisputably established. However, knowledge management should not be merely considered as yet another fashion or a new, lucrative activity area for advisory and consulting companies. Information processing obviously results in symmetry of information among organizations. On the other hand, asymmetry of knowledge is a fundamental attribute of organization's competitiveness in a postmodern age - in Bauman's sense. Therefore, a significant question arises in this framework: who is a subject and what is an object of organization's knowledge?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 159-173